PROSEDUR ADMINISTRSI PADA WEBSITE NDS DAN BRISPOT GUNA OPTIMALISA SI PEMODELAN BISNIS DI PT BANK RAKYAT INDONESIA (PERSERO) KANTOR CABANG PEMBANTU BATU - Muhammad Khulilurrohman; Ety Dwi Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Basically, the role of human resources who have good competence has a significant role in achieving a goal that has been designed by initiating the basic things in supporting the achievement of a goal that has been designed. Human resources refers to a method in a systematic approach to designing, directing, organizing and controlling every aspect related to workforce or what is commonly known as human resources in an agency. With the current conditions of the modern era, information technology systems have become an inseparable unit in aspects of human life. Technology has the potential prospect of changing the paradigm of data and correspondence administration from previously being general in nature to being more efficient, structured, fast or responsive to the company's performance needs.